Efeitos do alendronato de sódio e do ranelato de estrôncio na estrutura óssea do côndilo: estudo experimental em ratas submetidas à supressão hormonal - Pagani, Bruna Trazzi (2016)
Osteoporosis is a condition resulting from a deficiency in estrogen production, with higher incidence in postmenopausal women, and is characterized by reduced bone mass. The influence of osteoporosis in the mandibular condyle is not fully established in the literature, so the aim of this study was to evaluate the bone structure of the condyle in rats subjected to hormone suppression induced by ovariectomy. 108 Wistar rats divided into 2 groups were used. 1- Group OVX rats were subjected to ovariectomy, 2 SHAM group, the rats underwent the same surgery exposing the ovaries and then returning them intact to the original position and sutures for plans were made for the purpose of this procedure simulate surgical stress by performing the same steps of ovariectomy however were not the ovaries removed. Each group was subdivided into 3 groups of 18 animals each according to drug treatment: group NaCl, treated with saline 9%, ALD group, treated with Alendronate Sodium and Sr group treated with Ranelado Strontium. The treatments began 60 days after ovariectomy and extended until the date of euthanasia. After 30, 45 and 75 days of treatment, 6 animals in each group and subgroup (OVX NaCl, OVX ALD, OVX Sr, SHAM NaCl, SHAM ALD, SHAMSr) were euthanized and the part containing the condyle was removed for histomorphometric analysis. In the inter evaluation at 90 days, there is a reduction in bone volume in NaCl OVX group compared to the sham NaCl and OVX ALD and OVX Sr (p <0.05, ANOVA, Tukey test), indicating that the experimental model is adequate to study and proposed that both drugs act positively in maintaining bone structure after hormone suppression. But the comparison of OVX ALD groups and OXV Sr, there was no significant difference between study periods and between treated SHAM groups or not, indicating that the Sodium Alendronate and Strontium ranelate exhibit protective action of bone volume only in conditions hormone suppression and there is no difference between the effects